2021
DOI: 10.3390/s21082847
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Bokashi-Composting Process Using Effective Microorganisms-1 in Smart Composting Bin

Abstract: Malaysians generate 15,000 tons of food waste per day and dispose of it in the landfill, contributing to greenhouse gas emissions. As a solution for the stated problem, this research aims to produce an excellent quality bokashi compost from household organic waste using a smart composting bin. The bokashi composting method is conducted, whereby banana peels are composted with three types of bokashi brans prepared using 12, 22, and 32 mL of EM-1 mother cultured. During the 14 days composting process, the smart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…Their results indicate that the use of sheep manure and olive pumice improved the composting process of tomato waste. Lew et al [61] optimized the temperature, moisture content, humidity and volume of liquid phase during composting of food waste in a smart bokashi composting system by also using a factor-by-time approach. Li et al [62] estimated the optimal concentration of fulvic acid to improve the composting of straw and fungal residues based on the ANOVA analyzes of the experimental data, while Song et al [63] used ANOVA analyses of the experimental data for optimization of the composting of food waste.…”
Section: Agricultural Wastementioning
confidence: 99%
See 1 more Smart Citation
“…Their results indicate that the use of sheep manure and olive pumice improved the composting process of tomato waste. Lew et al [61] optimized the temperature, moisture content, humidity and volume of liquid phase during composting of food waste in a smart bokashi composting system by also using a factor-by-time approach. Li et al [62] estimated the optimal concentration of fulvic acid to improve the composting of straw and fungal residues based on the ANOVA analyzes of the experimental data, while Song et al [63] used ANOVA analyses of the experimental data for optimization of the composting of food waste.…”
Section: Agricultural Wastementioning
confidence: 99%
“…In addition, Sokač et al [24], presented the efficient use of the Box-Behnken experimental design (four variables at three levels) and response surface modelling (RSM) to optimize the composting process of biowaste in an adiabatic reactor with and without bioaugmentation. In addition to the optimization of the composting process, there are also examples of the application of the response surface methodology to optimize soil nutrient quality after compost addition (4-45% of compost based on soil weight) [60] and the application of RSM and artificial neural network (ANN) modeling to optimize the adsorption efficiency of municipal solid waste compost for the removal of reactive dyes from aqueous mixtures [61]. The results presented by Mazumder et al [68] showed that higher compost addition (>15%) increased the amount of nutrients in the soil over time, while Dehghani et al [69] stated that both RSM modeling and ANN modeling have a significant ability to describe and optimize the adsorption mechanisms.…”
Section: Agricultural Wastementioning
confidence: 99%
“…Kematangan bokasi dapat dilihat dari kandungan karbon dan nitrogen melalui rasio C/N nya (Kusmiyarti, 2013). Tingginya rasio C/N di dalam bahan organik dapat menyebabkan proses penguraian berlangsung lebih lama, sedangkan tingginya rasio C/ N pada bokasi menunjukkan bahwa bahan dasar bokasi belum terurai sempurna (Lew et al, 2021;Irfan et al, 2017;Suprianto, 2008). Rasio C/N bokasi pada penelitian ini berkisar 9,2-12,0 dengan rata-rata sebesar 10,4.…”
Section: Rasio C/nunclassified
“…Under conditions of native forests, the high microorganism population in the soil provides nutrients to the plants through organic matter degradation, phosphate solubilization, and nitrogen fixation (Rondina et al, 2019). The increase in fertilizers prices stimulates the search for alternatives sources, which allow improvements in the chemistry, biology, and physics of the soil with the use of residues such as Bokashi compost (Viana et al, 2020), obtained from the action of microorganisms in the organic matter, simulating natural ecosystems (Lew et al, 2021).…”
mentioning
confidence: 99%
“…Under natural conditions, the activity of microorganisms contributes to the biomass decomposition, nutrients cycling, respiration, and soil structuring, sustaining the ecosystem (Rondina et al, 2019;Lew et al, 2021), so the utilization of fermented composts may act as a source of microorganisms benefiting the production of the agricultural system. According to Bononi et al (2020), the utilization of microorganisms allows an increment of up 41% in the growth rate and 141% in the efficiency of phosphorus absorption by soybean.…”
mentioning
confidence: 99%